Innovation in multinational corporations in the information age : the experience of the European ICT industry - Santangelo, Grazia D. (Cheltenham, U.K. ; Northampton, Mass.: Edward Elgar Pub., 2002)
This title investigates the production of information communication technology (ICT) through multinational corporations worldwide, and particularly in Europe. Questions relating to the management of corporate technological portfolio and the management of corporate research activity are addressed, and sectoral specialization along with the geographical location of corporate technological development are analysed. It shows viewpoints on the changing boundaries of the international firm and the evolution of corporate learning in a more complex technological system. The increasing significance of regions as units of spatial competition is highlighted, and the analysis of ICT provides an insight into business strategy and policy making agendas.
Includes bibliographical references (p. 191-217) and index.
rpm 07/09/16
Loans
Keywords: Technological innovations; International business enterprises; Information technology; Europe